Penerapan Model Pembelajaran Discovery Learning Terhadap Kemampuan Berpikir Kritis dan Literasi Sains Peserta Didik Pada Konsep Pencemaran Lingkungan - Mustikasari, Ane; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Edubiologica, 2023)
Critical thinking skills and scientific literacy are known to be low because the learning process does not involve students so that students are les active in participating in learning. This research was conducted with the aim of improving students critical thinking skillss and scientific literacy on the concept of envinomental pollution. The research method used in this study was quasi experimental with a two group pretest posttest design. Sampling was done by using random sampling technique. The research sample was students of class X MIA MAN 2 Tasikmalaya City. The instrument used in this study was as critical thinking ability description test sheet as many as 13 queation, LKPD to measure scientific litteracy, and a student response questionaire sheet to learning. The data analysis technique used was t test with a significantion of the level of 0.05. The conclusion of this study is the effect of discovery learning learning models on students' critical thinking skills and scientific literacy on the concept of environmental pollution Bio Educatio Vol. 7 No. 2 April 2022 | 2 (experimental study in class X MAN 2 Tasikmalaya City in 2021/2022). The results of the study show that the Discovery learning model can improve students' critical thinking skills as indicated by the average gain value. This is supported by the response of students who gave a percentage score of 94% which indicates that the response of students to learning is very positive and really likes learning using the discovery learning model on the concept of environmental pollution.